Transforming health systems through good digital health governance. (Sustainable development working papers., 2018)
Information and communication technology (ICT) in health systems or digital health can accelerate health system reforms for better quality, efficient, and accessible patient-centered care. Digital health has been acknowledged as a building block for universal health coverage. However, many countries still lack a holistic approach to digital health. This paper highlights efforts to develop a health ICT governance architecture framework through consultations and close collaboration with experts. The framework is expected to meet the evolving needs of developing member countries on digital health. Technology will continue to impact the region as broadband and mobile coverage become increasingly prevalent. By 2015, 2.5 billion people were mobile phone subscribers, with 600 million new subscribers expected by 2020.